Conductometric studies of the thermodynamics for complexation of 1,1-diethyl-3-(4-methoxybenzoyl)thiourea and cobalt(II) cation in aqueous binary mixtures of polar organic solvents - Suhud K.; Heng L.Y.; Rezayi M.; Al-Abbasi A.A.; Hasbullah S.A.; Ahmad M.; Kassim M.B. (Springer New York LLC, 2024)
The complexation reaction of Co2+ (M) and the 1,1-diethyl-3-(4-methoxybenzoyl)thiourea (L) ligand in the binary mixtures: acetonitrile-dimethylsulfoxide (MeCN-DMSO), acetonitrile-dichloromethane (MeCN-DCM), water-dimethylsulfoxide (H2O-DMSO) and acetonitrile-water (MeCN-H2O), was investigated using a conductometric method at temperatures of (288.15, 298.15, 308.15 and 318.15) K. In all cases, the conductance data showed that the stoichiometry of the neutral complex formed between M and L is 1:3 [M:3L], which indicates that the Co2+ ion was oxidized to Co3+ during the reaction. The best estimate of the stability constant, log10 K f, = 3.31 for the [CoL3] complex, was observed with the MeCN-DCM (20:80 %) binary mixture at 298.15 K. The values of the thermodynamic parameters (i.e., ?Gc and ? Sc) for the formation of the [CoL3] complex were obtained from the temperature dependence of the stability constant via van't Hoff plots. The results show that, in most cases, the [CoL3] complexes are enthalpy destabilized but entropy stabilized. The values and signs of the thermodynamic parameters are affected by the nature and composition of the mixed solvents but are independent of the temperature. 2015 Springer Science+Business Media New York.